2010
DOI: 10.1080/07317101003776449
|View full text |Cite
|
Sign up to set email alerts
|

Does Teaching Problem-Solving Skills Matter? An Evaluation of Problem-Solving Skills Training for the Treatment of Social and Behavioral Problems in Children

Abstract: Parent training combined with problem solving skills training has been proposed as a comprehensive treatment for childhood oppositional behaviors, poor child social skills, and parental stress . The current study compared Parent Training + Problem Solving Skills Training with a Parent Training + nondirective condition. Parents of 32 children first attended Parent Training . After the parents completed Parent Training, children were randomly assigned to individual therapy in either a Problem Solving Skills Trai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 57 publications
1
1
0
Order By: Relevance
“…The results suggest that fathers with better overall problem-solving skills are less likely to be distressed in relation to their roles as parents, both generally and in the context of their child's T1D management. These findings are consistent with those in past research, which indicated that for parents (i.e., mostly mothers) of children with various physical and psychological conditions, the use of problem-solving skills is associated with less parenting stress (Bushman and Peacock, 2010;Martin et al, 2013;Noojin and Wallander, 1997). Relatedly, there is support for the idea that maladaptive coping strategies (e.g., avoidance and disengagement), in contrast to more adaptive coping skills like problem-solving, are associated with increased parenting stress when a child has a chronic illness (Jaser et al, 2014;Kumari et al, 2011).…”
Section: Discussionsupporting
confidence: 92%
“…The results suggest that fathers with better overall problem-solving skills are less likely to be distressed in relation to their roles as parents, both generally and in the context of their child's T1D management. These findings are consistent with those in past research, which indicated that for parents (i.e., mostly mothers) of children with various physical and psychological conditions, the use of problem-solving skills is associated with less parenting stress (Bushman and Peacock, 2010;Martin et al, 2013;Noojin and Wallander, 1997). Relatedly, there is support for the idea that maladaptive coping strategies (e.g., avoidance and disengagement), in contrast to more adaptive coping skills like problem-solving, are associated with increased parenting stress when a child has a chronic illness (Jaser et al, 2014;Kumari et al, 2011).…”
Section: Discussionsupporting
confidence: 92%
“…That they feel competent in solving the problem makes positive contribution to their problem-solving skills (Korkut, 2017;Yenice, 2012). Some studies revealed that having problem solving skill has an effect on decrease in aggression, anger, hostility (Seçer & Ogelman, 2011) and in negative behaviors (Bushman & Peacock, 2010), and on increase in social self-efficacy (Erözkan, 2013), positive emotion (D'Zurilla, Maydeu-Olivares, & Pujol, 2011) and interpersonal relationships (Joseph & Strain, 2010;Sumi, 2012). Negative thinking is referred to as negative approach to the problem.…”
Section: Introductionmentioning
confidence: 99%